Pengaruh Profitabilitas, Likuiditas, Solvabilitas, Nilai Pasar dan Kebijakan Dividen Terhadap Return Saham (Jurnal Kendali Akuntansi, 2025)
This research aims to examine the effect of profitability, liquidity, solvency, market value and dividend policy on stock returns in companies that are consistently included in the LQ45 index for the period 2020 to 2023. The determination of the research sample of 18 companies was carried out using the purposive sampling method. Meanwhile, for hypothesis testing and research instruments using multiple linear regression analysis tools with SPSS software. The results of the study prove that proitability, liquidity, solvabiity, market value and dividen policy has no effect on stock returns